Malay Traditional Woodcarving Artefacts in Nik Rashiddin’s Personal Collection at Kandis, Kelantan. - Zawiyah Baba (2005)
The special collection of traditional Malay woodcarving at Kandis Kelantan was the legacy of the late Nik Rashiddin Nik Hussein, master carver, collector and philosopher (1955 – 2002). He was well known particularly for the fine keris hilts of his later years as a carver, his quest for a Malay identity in woodcarving. The beautifully illustrated catalogue of the Spirit of Wood or Semangat Kayu exhibition held in Singapore, London and Kuala Lumpur from 2003 to 2005, highlighted Nik Rashiddin’s work and was the first attempt to document artefacts in the collection. The ATMA UKM project documented and digitised Nik Rashiddin’s collection of artefacts, a substantial part of the keris collection, as well as sketches, drawings, books and newspaper cuttings. In addition, a digital database was constructed to facilitate wider and easier access to the collection. An international seminar on Malay Woodcarving – the Legacy of Nik Rashiddin held on 24 -26 November 2008 at Kandis, Kelantan produced 18 working papers on NIk Rashiddin’s collection and work and on Malay woodcarving in general.